2011
DOI: 10.1080/09500340.2011.581767
|View full text |Cite
|
Sign up to set email alerts
|

Nondistillability of distillable qutrit–qutrit states under depolarising noise

Abstract: We study the effects of decoherence on some particular bipartite qutrit states under the influence of global, collective, local and multilocal depolarising noise. We show that certain free entangled distillable qutrit density matrices become bound entangled or separable and hence convert into nondistillable density matrices in global noise. The collective noise increases the degree of entanglement of the qutrit bipartite states. Furthermore, we show that some particular local operation cannot avoid the nondist… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…[24] Similar work has been reported on the two-qutrit system interacting with global, local, and multilocal depolarizing noise. [25] Further study was performed in the case of being under thermal reservoirs. [26,27] In addition, the DSD for two-qutrit systems in the presence of an external magnetic field and Dzyaloshinskii-Moriya interaction under decoherence was also investigated.…”
mentioning
confidence: 99%
“…[24] Similar work has been reported on the two-qutrit system interacting with global, local, and multilocal depolarizing noise. [25] Further study was performed in the case of being under thermal reservoirs. [26,27] In addition, the DSD for two-qutrit systems in the presence of an external magnetic field and Dzyaloshinskii-Moriya interaction under decoherence was also investigated.…”
mentioning
confidence: 99%
“…All these fundamental issues can be extended beyond qubits. Quantum discord in higher dimensions has been elusive, and little is known about calculations beyond two dimensional systems 32 33 34 35 36 .…”
mentioning
confidence: 99%
“…[18] This phenomenon was later also studied for qutrit-qutrit systems interacting with zero-temperature reservoirs, [20] thermal reservoirs [21,22] and under depolarizing noise. [23] In particular, it was shown that whenever there is ESD [4] in the principal system, there is always a corresponding entanglement sudden birth (ESB) among reservoirs. [12] With these previous findings in mind, we raise and answer the following question.…”
mentioning
confidence: 99%